Citizens' perceptions of justice in international climate policy: Empirical insights from China, Germany and the US - Joachim Schleich; Elisabeth Dütschke; Claudia Schwirplies; Andreas Ziegler (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
Relying on a recent survey of more than 3300 participants from China, Germany and the US, this paper empirically analyzes citizens' perceptions of climate change and climate policy, focusing on key guiding principles for sharing mitigation costs across countries. The ranking of the main principles for burden-sharing is identical in China, Germany and the US: accountability followed by capability, egalitarianism, and sovereignty. Thus, on a general level, citizens across these countries seem to have a common understanding of fairness. We therefore find no evidence that citizens' (stated) fairness preferences are detrimental to future burden-sharing agreements. While there is heterogeneity in citizens' perceptions of climate change and climate policy within and across countries, a substantial portion of citizens in all countries perceive a lack of transparency, fairness, and trust in international climate agreements.
urn:nbn:de:0011-n-2791268
Keywords: 330; climate policy; climate change; burden-sharing; equity; fairness; distributive justice; trust; public opinion